(untitled) - Johnson, George B. (New York, 2006)
George Johnson’s textbook has often been considered a student favorite. Dr. Johnson has written this non-majors textbook from the ground up to be an engaging and accessible learning tool with an emphasis on "how things work and why things happen the way they do". This authoritative textbook features a straightforward, clear writing style and a wide variety of media assets to enhance the content of the textbook.
Keywords: Biology,Sinh vật học